The heterogeneous response of real estate asset prices to a global shock - Sandro Heiniger; Winfried Koeniger; Michael Lechner (Goethe University Frankfurt, Center for Financial Studies (CFS), 2022)
We estimate the transmission of the pandemic shock in 2020 to prices in the residential and commercial real estate market by causal machine learning, using new granular data at the municipal level for Germany. We exploit differences in the incidence of Covid infections or short-time work at the municipal level for identification. In contrast to evidence for other countries, we find that the pandemic had only temporary negative effects on rents for some real estate types and increased asset prices of real estate particularly in the top price segment of commercial real estate.
Keywords: E21; E22; G12; G51; R21; R31; 330; Real estate; Asset prices; Rents; Covid pandemic; Short-time work; Affordability crisis